Messy adventure - "Cowley, Joy" (Auckland; Clean Slate Press, 2008)
Ross Beansack, the big hairy author, is writing a book about saving the rainforests. His very modern publisher says people can't write about something they haven't experienced. "Simple," says Sophie, Ross's seven-year old neice. "Just take the number 23 bus." But Ross Beansack is caught up in a recycling catastrophe of his own. Suggested level: primary
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Humorous fiction